Up-Converting Nanoparticle-Based Immunochromatographic Strip for Multi-Residue Detection of Three Organophosphorus Pesticides in Food - Zou, Rubing; Chang, Yunyun; Zhang, Tianyi; Si, Fangfang; Liu, Ying; Zhao, Ying; Liu, Yihua; Zhang, Mingzhou; Yu, Xiaoping; Qiao, Xusheng; Zhu, Guonian; Guo, Yirong (Frontiers in Chemistry, 2019)
Organophosphorus (OP) pesticides are widely used to control pest because of their high activity. This study described a rapid and sensitive lateral flow immunochromatographic (LFIC) assay based on up-converting nanoparticles (UCNPs) for multi-residue detection of three OP pesticides. The developed assay integrated a novel fluorescent material UCNPs labeled with a broad-specific monoclonal antibody. Based on the competitive platform by immobilized antigen in the test zone, the optimized UCNPs-LFIC assay enabled sensitive detection for parathion, parathion-methyl and fenitrothion with IC50 of 3.44, 3.98 and 12.49 ng/mL (R2≥0.9776) within 40 min. The detectable ability ranged from 0.98 to 250 ng/mL. There is no cross-reactivity with fenthion, phoxim, isocarbophos, chlorpyrifos and triazophos even at a high concentration of 500 ng/mL. Matrix interference from various agricultural products was also studied in food sample detection. In the spiked test, recoveries of three OP pesticides ranged from 67% to 120% and relative standard deviations were below 19.54%. These results indicate the proposed strip assay can be an alternative screening tool for rapid detection of three OP pesticides in food samples.